REVERSE ENGINEERING MICROSERVICES USING SINGLE SOURCE OF TRUTH FOR ENHANCED INSIGHTS - Awan, Muhammad Waqar Ul Hassan (MEng project report (CAS), 2025)
Software maintenance, such as debugging and issue resolution, is a key part of the software development process. However, maintaining an extensive software system with multiple interconnected components is easier said than done. One approach to improving software maintenance is reverse engineering the system for more straight- forward analysis and insights. This report presents a comprehensive framework that reverse engineers the static source code into a visualized format by centralizing key information artifacts from the software in one place. The study demonstrates this approach using an actual software application and real-world use cases. This method aids the maintenance process by providing valuable insights and facilitating analysis.
Keywords: reverse engineering; software engineering; microservices